Structure-function relationships for the selective inhibition of human 3β-hydroxysteroid dehydrogenase type 1 by a novel androgen analog. Issue 174 (November 2017) - Pham, Jenny H.; Will, Catherine M.; Mack, Vance L.; Halbert, Matthew; Conner, Edward Alexander; Bucholtz, Kevin M.; Thomas, James L.
Graphical abstract: Highlights: Arg195 in human 3β-HSD1 is a key amino acid target for selective inhibition. 16-Cyano-17-keto-trilostane is a novel, selective inhibitor of 3β-HSD1. Selective inhibition of 3β-HSD1 may prevent spontaneous premature birth. Inhibition of 3β-HSD1 decreases placental estradiol production that promotes labor. The 3β-HSD1 inhibitor may be administered with 17α-hydroxyprogesterone caproate. Abstract: 3β-Hydroxysteroid dehydrogenase type 1 (3β-HSD1) is selectively expressed in human placenta, mammary glands and breast tumors in women. Human 3β-HSD2 is selectively expressed in adrenal glands and ovaries. Based on AutoDock 3 and 4 results, we have exploited key differences in the amino acid sequences of 3β-HSD1 (Ser194, Arg195) and 3β-HSD2 (Gly194, Pro195) by designing a selective inhibitor of 3β-HSD1. 2, 16-Dicyano-4, 5-epoxy-androstane-3, 17-dione (16-cyano-17-keto-trilostane or DiCN-AND) was synthesized in a 4-step procedure from androstenedione. In purified 3β-HSD inhibition studies, DiCN-AND competitively inhibited 3β- HSD1 with Ki  = 4.7 μM and noncompetitively inhibited 3β-HSD2 with a 6.5-fold higher Ki  = 30.7 μM. We previously reported similar isoenzyme-specific inhibition profiles for trilostane. Based on our docking results, we created, expressed and purified the chimeric S194G-1 mutant of 3β-HSD1. Trilostane inhibited S194G-1 (Ki  = 0.67 μM) with a noncompetitive mode compared to its 6.7-fold higher affinity, competitive inhibition of 3β-HSD1 (Ki  = 0.10 μM). DiCN-AND inhibited S194G-1 with a 6.3-fold higher Ki (29.5 μM) than measured for 3β-HSD1 (Ki  = 4.7 μM) but with the same competitive mode for both enzyme species. Since DiCN-AND noncompetitively inhibits 3β-HSD2, which has the Gly194 and Pro195 of 3β-HSD2 in place of the Ser194 and Arg195 in 3β-HSD1, this suggests that Arg195 alone in 3β-HSD1 or S194G-1 is required to bind DiCN-AND in the substrate binding site (competitive inhibition). However, both Ser194 and Arg195 are required to bind trilostane in the 3β-HSD1 substrate site based on its noncompetitive inhibition of S194G-1 and 3β-HSD2. In support of this hypothesis, DiCN-AND inhibited our chimeric R195P-1 mutant noncompetitively with a Ki  = 41.3 μM (similar to the 3β-HSD2 inhibition profile). Since DiCN-AND competitively inhibited S194G-1 that still contains R195 but noncompetitively inhibited R195P-1 that still contains S194, our data provides strong evidence that the Arg195 being mutated to Pro195 (as present in 3β-HSD2) shifts the inhibition mode from competitive to noncompetitive in 3β-HSD1. This supports the key role of Arg195 in 3β-HSD1 for the high affinity, competitive binding of the trilostane analogs. Our new structure/function information for the design of targeted 3β-HSD1 inhibitors may lead to important new treatments for the prevention of spontaneous premature birth.